ASSESSMENT OF THE REGION'S INVESTMENT ENVIRONMENT AND POLICY INSTRUMENTS FOR THE IMPLEMENTATION OF ITS INVESTMENT POTENTIAL IN WARTIME - Ruslan Boiko; Roman Martsenyuk; Arsen Protsykevych (Baltic Journal of Economic Studies)
The subject of the study is the processes of formation and implementation of regional investment policy in wartime. Methodology. The following methods of economic analysis were used in the study: analysis and synthesis (to ensure a systematic approach when characterising the investment environment of the region), statistical analysis and calculation (when analysing the volume, dynamics and structure, factors and functional features of the formation of the investment environment of the regional economy), strategic management (to determine the strategic goal, objectives, mechanisms, instruments and expected results of the regional investment policy in wartime). The article is aimed at characterising the state of the investment environment of the region and substantiating the instruments for realisation of the investment potential of the region in wartime (on the example of Lviv Oblast of Ukraine). The results of the study enabled the identification of the strengths and weaknesses, as well as the opportunities and threats, of the region's investment environment in terms of components such as production and resources, institutional and legal, security, infrastructure and macroeconomic. In particular, the article finds that the production and resource, safety and macroeconomic components of the region's investment environment are at a relatively high level. Instead, the institutional, legal and infrastructural components are characterised by greater problems (and thus a negative impact on the intensification and improvement of the structural characteristics of investment activity). Conclusion. The Lviv Oblast has been shown to exhibit several distinguishing features when compared to other regions of Ukraine. These include a relatively large domestic market and a high level of development in the real sector, including financial and credit, and investment infrastructure, transport, logistics, and trade systems, construction, education, scientific and ICT potential, and a large population. The region's strategic location has also contributed to the influx of substantial capital investment, which has been allocated to the regional economy, particularly to real sector industries, productive sectors, and areas with a high level of added value. This indicates that the region's investment development is at a relatively high level. At the same time, the following shortcomings and weaknesses remain in the region's investment development: the presence of systemic deficiencies in the region's investment climate; small volumes of investment (per unit of resources) and limited rates of their increase; low investment activity in the real sector of the economy with high added value; low investment in intangible assets in industries that form human and innovative potential; critically low volumes of foreign investment, especially direct investment; limited public, intermunicipal and cross-border investment; underdeveloped system of risk financing of investment in innovation; underdeveloped stock market and small role of bank lending. It is substantiated that effective instruments of regional investment policy in the context of critical instability are: military risk insurance and diversification; use of concession agreements; private and public investments in the defence industry and critical infrastructure industries/sectors (energy, transport and logistics, medicine and pharmaceuticals, natural resources); support for innovative and technological startups in the areas of security, the real economy and infrastructure; stimulation of investments in human resources; support for investments in business projects of demobilised persons, war veterans and other combatants; encouragement of investments in the development of export potential to maintain the country's financial security.